The Fuzzy Front End of New Product Development for Brazilian Technology-Based Companies in the Medical Device Industry: a Causal Model - Mendes, Glauco H.S.; de Toledo, José Carlos (Brazilian Journal of Operations & Production Management, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->The Fuzzy Front End (FFE) is considered the first stage of New Product Development (NPD). The fuzzy front end decisions have great impact on product quality, costs, and time spent on new product projects. This paper seeks to identify which fuzzy front end activities and practices contribute the most to new product success of Brazilian Technology-Based Companies (TBCs) in the medical device industry and to provide a causal model for the fuzzy front end of new product development. The data were obtained by a survey carried out in 30 small companies including 49 new product projects. The companies were requested to choose new successful and unsuccessful product projects. The results demonstrate that successful projects are distinguished from unsuccessful projects due the follow practices: marketing orientation, the company competence to translate client needs into product characteristics, proficiency in idea generation, the interface between Marketing and R&D in the fuzzy front-end and the role performed by the leader project. Having got these findings, it was possible to propose a causal model with the critical success factor in four dimensions: strategic; process; organization; and leadership.